Navigating the Fourth Industrial Revolution: SBRI - A Comprehensive Digital Maturity Assessment Tool and Road to Industry 4.0 for Small Manufacturing Enterprises - Volf, Ludek; Dohnal, Gejza; Beranek, Libor; Kyncl, Jiri (Manufacturing Technology Journal, 2024)
This article presents the development and validation of SBRI (Small Business Digital Maturity Assessment and Road to Industry 4.0), an innovative methodology for assessing digital maturity and supporting digital transformation specifically designed for small manufacturing enterprises in the context of Industry 4.0. Unlike existing models, which are often too complex or unsuitable for smaller organizations, SBRI considers the unique characteristics and constraints of small businesses. The methodology includes five key dimensions: Strategy, Technology, Process, People, and Organization, elaborated into 25 subdimensions with specific maturity criteria and indicators. The SBRI includes a structured roadmap for digital transformation through a proposed digital maturity continuous improvement cycle. An empirical study involving 23 small manufacturing enterprises in the Czech Republic has demonstrated the validity and practical applicability of the methodology. The results showed an average level of enterprise digital maturity of 0.9 on a scale of 0 - 4. These findings suggest that small businesses are just at the beginning of their digital transformation journey. Therefore, the SBRI methodology represents a valuable tool for navigating small businesses through their digital transformation journey, contributing to academic discourse and practical application of Industry 4.0 principles in the small business segment.
Keywords: Digital maturity assessment; Industry 4.0; Small manufacturing enterprises; Digital transformation; SBRI methodology